Linking Online Reviews, Personal And Environmental Factors And Diners’ Intention To Eat Out - Mohammad Shahid, Nur Nadirah (2024)
The concept of ‘eating out’ has changed as an important area of study within the food service industry with the growth of social media (SM) platforms. Even though research on online reviews from SM has been increasing in recent years, empirical evidence is scarce on online reviews and their consequences on diners’ intention to eat out. Two theories were applied to underpin this study, which is Heuristic-Systemation Information Processing Model (HSM) and Social Cognitive Theory (SCT). This study examines the effects of online reviews (i.e., argument quality, source credibility, and perceived quantity of online reviews) on diners’ intention to eat out, the relationship between personal and environmental factors with diners’ intention and the influence of argument quality on these factors. Moreover, this study investigates the mediation effects of argument quality to the relationship between source credibility and perceived quantity of reviews with diners’ intention to eat out. Thus, 12 hypotheses are proposed. Cross-sectional design and quantitative approach were employed. The study used an online survey to collect data on Malaysian diners with an SM account and experience reading online reviews. The respondents were approached through various SM platforms. A purposive sampling technique was used to collect data. Two hundred thirty-six useful responses were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS software. The results showed that all hypotheses are supported except for H4, H10, and H12. The argument quality was found to have relationships with other online review variables and personal and social influence.